Implementasi Model Pembelajaran Invitation dan Greeting Card dalam Pembelajaran Bahasa Inggris Siswa Kelas VIII SMP Negeri 16 Semarang - Mursyida, Fairus Fathin Mursyida; Annury , Muhammad Nafi; Abdullah , Shodiq Abdullah; Syamsuddin , Muhammad Syamsuddin; Syamsuddin, Muhammad Syamsuddin (Universitas Muhammadiyah Makassar, 2026)
The Merdeka Curriculum promotes authentic and communicative approaches in English language teaching. However, empirical research examining how functional text tasks are pedagogically enacted in junior secondary EFL classrooms remains limited, particularly from a qualitative, process-oriented perspective. This study analyzes the implementation of invitation and greeting card tasks and explores how these practices were associated with the construction of learning quality in the classroom. An instrumental qualitative case study design was employed, with data collected through classroom observations, semi-structured interviews, and analysis of instructional documents and student artifacts over an eight-week instructional unit. The findings indicate that authentically framed and contextually grounded functional text tasks were associated with sustained student engagement, emerging pragmatic awareness, and peer-mediated interaction. Learning quality in this case was not attributed to task type alone; rather, it was found to be constructed through the interplay of task design, pedagogical mediation, and classroom social dynamics. The study contributes a process-oriented account of how communicative competence was mediated through functional text pedagogy at the junior secondary level. Practically, the findings offer insights into authentic task design and scaffolding strategies within the Merdeka Curriculum framework.